Who benefits from aid for trade? Comparing the effects on recipient versus donor exports - Philipp Hühne; Birgit Meyer; Peter Nunnenkamp (Kiel Institute for the World Economy (IfW), 2013)
Recent studies offer an ambiguous picture on the effectiveness of foreign aid in strengthening the export capacity of recipient countries. Moreover, the literature on aid for trade (AfT) has often neglected that exporters in the donor countries may be among the main beneficiaries. We hypothesize that AfT is as much in the self-interest of donor countries as it may have promoted the exports of recipient countries. We simultaneously estimate and compare the effects of AfT on trade in both directions. We find that AfT increases recipient exports to donors as well as recipient imports from donors. The first effect tends to dominate the latter, which contradicts the skeptical view that donors grant AfT primarily to promote their own export interests.
Keywords: F35; F14; 330; aid effectiveness; aid for trade; recipient exports; donor exports